Pengaruh Persepsi Masyarakat Dan Potensi Penerimaan Negara Terhadap Kebijakan Ekstensifikasi Objek Cukai Minuman Bergula Dalam Kemasan Di Kota Bekasi - Star, Yurisman; Bahri, Salsabila Amirah; Prihadini, Diana (Jurnal Ilmu Administrasi Publik, 2024)
The tax extensification policy on Excise Objects is a governmentdiscourse that will be released in 2024. The addition of excisable goods to packaged sugary drinks is highly considered. One aspect that supports the success of a policy is acceptance and support from the community. The key factor in the successful implementation of this excise tax is the level of acceptance from the community. However, it is also related to the government that wants this policy to be a significant potential state revenue. This study aims to determine the Influence of Public Perception and Potential State Revenue on Excise Object Extensification Policy The research method used is a quantitative-descriptive method. Data collection techniques using research instruments are in the form of questionnaires and literature. The population in this study is the Bekasi city community. The sampling technique in this study is Probability sampling with this method sampling the population with as many as 150 samples. And analyzed using multiple linear regression analysis using the help of IBM Statistical Software Version 29.0. The results of this study show that Public Perception influences the MBDK Excise Object Extensification Policy by 36.4%. The potential state revenue has an influence of 34.8% on the MBDK Excise Object Extensification Policy. Public Perception and State Revenue Potential affect the MBDK Excise Object Extensification Policy variable simultaneously with a value of 0.406 or 40.6%. Of these, 59.4% were explained by other factors that were not included in the study.